Answer: -2
Explanation:
We know that the slope of a secant line over a interval [a,b] is given by :-
![m=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ziuz50bstzpbjca0f6kopslrmiqk0ylmg2.png)
Given f(x) =
![-2x^2 + 4](https://img.qammunity.org/2021/formulas/mathematics/college/lhqr4mbsm1384kdpzkg430ke03fjatj4wz.png)
Then, the slope of the secant line over the interval [-1, 2] is given by :-
![m=(f(2)-f(-1))/(2-(-1))\\\\=((-2(2)^2+4)-(-2(-1)^2+4))/(2+1)\\\\=((-2(4)+4)-(-2(1)+4))/(3)\\\\=((-8+4)-(-2+4))/(3)\\\\=(-4-2)/(3)\\\\=(-6)/(3)\\\\=-1](https://img.qammunity.org/2021/formulas/mathematics/college/9r2pbin3kstakdt8v8fmkmrhah8gijds5c.png)
Hence, the slope of the secant line over the interval [-1, 2] is -2.